Evaluating usability of learning disability assessment system - Harnum Junaidi, Putri Sakinah Fikriah; Imi, Nur Amira; Zakaria, Noor Azura; Abdul Karim, Ruwinah; Lubis, Muharman; Mat Rejab, Mazidah (IEEE, 2022)
The Learning Disability Assessment System (LeDAS) entails crucial decision making to produce a diagnosis referring to the information inserted by the therapists and parents. In this manner, accuracy of the information system is a pivot to generate an effective system. Research evaluation of LeDAS is necessary due to the fact that it is a recently developed system with over 3,000 patients currently using it thus it is imperative to evaluate the system to measure its usability. The purpose of this research is to evaluate the usability of the developed LeDAS web-based system in order to ensure the system can fulfill the user’s satisfaction and be usable. The conducted survey targets therapists and parents to collect data. The data produced from this study will be used to provide insight into the need of furthering proficiency in generating a satisfactory system. This evaluation analyzed using the descriptive statistic, exploratory factor analysis (EFA), reliability testing and hypothesis testing. The result showed that 5 hypotheses were supported.